Failure Analysis for Teeth Broken of a Gearbox - Donghai Gao (Jixie chuandong)
Abstract For the phenomenon of broken teeth in the transmission， the causes are analyzed. The gear raw materials chemical composition， non-metallic inclusions， heat treatment hardness， carburized layer thickness， metallographic structure are checked. The metallographic structure of the abnormal wear site indicated that the friction burns have occurred. Combining with the characteristics of gearbox， the No.1 crack is considered to be the fatigue crack source of gear hub cracking. The gear hub cracking destroys the meshing relationship， reduce the bending fatigue strength， and cause teeth breakage. The analysis of assembly relationship of layshaft assembly， the axis clearance eliminated because of the synchronizer hub position shifting is the cause of tooth fracture. For gearbox shaft assembly included many components， correct assembly relationship between each other， and reliable fixation of assembly position have an important influence on the reliability of gear.